Neuronal circuits involved in osmotic challenges - Dos Santos Moreira, M. C.; Naves, L. M.; Marques, S. M.; Silva, E. F.; Rebelo, A. C.S.; Colombari, E. [UNESP]; Pedrino, G. R. (Institute of Physiology of the Czech Academy of Sciences, 2017)
The maintenance of plasma sodium concentration within a narrow limit is crucial to life. When it differs from normal physiological patterns, several mechanisms are activated in order to restore body fluid homeostasis. Such mechanisms may be vegetative and/or behavioral, and several regions of the central nervous system (CNS) are involved in their triggering. Some of these are responsible for sensory pathways that perceive a disturbance of the body fluid homeostasis and transmit information to other regions. These regions, in turn, initiate adequate adjustments in order to restore homeostasis. The main cardiovascular and autonomic responses to a change in plasma sodium concentration are: i) changes in arterial blood pressure and heart rate; ii) changes in sympathetic activity to the renal system in order to ensure adequate renal sodium excretion/absorption, and iii) the secretion of compounds involved in sodium ion homeostasis (ANP, Ang-II, and ADH, for example). Due to their cardiovascular effects, hypertonic saline solutions have been used to promote resuscitation in hemorrhagic patients, thereby increasing survival rates following trauma. In the present review, we expose and discuss the role of several CNS regions involved in body fluid homeostasis and the effects of acute and chronic hyperosmotic challenges.
Keywords: Acute hyperosmotic challenge; Body fluid homeostasis; Chronic hyperosmotic challenge; Osmosensory areas